Análise da viabilidade econômica e financeira da substituição de transformadores convencionais por transformadores com núcleo de metal amorfo, considerando os efeitos regulatórios sobre o investimento - Gustavo Soares Martins da Costa (2011)
This work studies the energy savings obtained by replacing conventional distribution transformers, with grain-orientated (CGO) steel cores, by transformers with amorphous material core. The substitution is supposed to take place gradually, during a long time. The energy and demand gains that could be obtained are determined and a monetary valuation is accomplished. Transformers losses data given by the ABNT NBR 5440:1999 rule, from the 2011 review project of NBR 5440, are used. For cores of amorphous material there are no rules, therefore, typical losses provided in the literature are used. The economic assessment of the transformers substitution project is based on a cash flow model, which considers the effects of the Brazilian Distribution Electricity Sector regulation. The analysis is based on real data from a Brazilian distribution utility. Obtained results indicate energy savings of 5,59 TWh and demand savings of 793,78 MW.